ZmEREB46, a maize ortholog of Arabidopsis WAX INDUCER1/SHINE1, is involved in the biosynthesis of leaf epicuticular very-long-chain waxes and drought tolerance. (August 2022) - Yang, Yue; Shi, Jianxin; Chen, Limei; Xiao, Wenhan; Yu, Jingjuan
Abstract: The aerial surfaces of plants are covered by a layer of cuticular wax that is composed of long-chain hydrocarbon compounds for protection against adverse environmental conditions. The current study identified a maize ( Zea mays L.) APETALA2/ethylene-responsive element-binding protein (AP2/EREBP)-type transcription factor, ZmEREB46. Ectopic expression of ZmEREB46 in Arabidopsis increased the accumulation of epicuticular wax on the leaves and enhanced the drought tolerance of plants. The amounts of C24/C32 fatty acids, C32/C34 aldehydes, C32/C34 1-alcohols and C31 alkanes in zmereb46 (ZmEREB46 knockout mutant) leaves were reduced. The amount of leaf total epicuticular wax decreased approximately 50% in zmereb46 . Compared to wild-type LH244 leaves, the cuticle permeability of zmereb46 leaves was increased, which resulted from decreased epicuticular wax load and a thinner cuticle layer. ZmEREB46 had transcriptional activation activity and directly bound to promoter regions of ZmCER2, ZmCER3.2 and ZmKCS1 . The zmereb46 seedlings also exhibited reduced drought tolerance . These results, and the observations in ZmEREB46 -overexpressing lines, suggest that ZmEREB46 is involved in cuticular metabolism by influencing the biosynthesis of very-long-chain waxes and participates in the cutin biosynthesis pathway. These results are helpful to further analyze the regulatory network of wax accumulation in maize. Highlights: ZmEREB46 is a member of the AP2/EREBP transcription factor family. ZmEREB46 affects wax deposition and drought tolerance in maize and Arabidopsis . ZmEREB46 regulates very-long-chain wax biosynthesis-related genes. A regulatory network of wax biosynthesis optimizes the plant drought response